Ni3Ga0. 8Pt0. 2 / CC catalyst as well as preparation method and application thereof
The Ni3Ga0.8Pt0.2 catalyst was loaded and thermally decomposed by wet impregnation method, and Ni3Ga0.8Pt0.2/CC catalyst was prepared, which solved the problems of insufficient activity and poor stability of the existing ternary alloy catalyst, and achieved efficient electrocatalytic performance in an alkaline environment.
Patent Information
- Application Number
- CN202510071049.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The existing ternary alloy catalysts have insufficient activity, poor stability, and easy dissolution or oxidation in acidic or alkaline electrolytes in hydrogen production reactions, which limits their development in large-scale applications.
The Ni3Ga0.8Pt0.2 catalyst was loaded on the carbon cloth by wet impregnation method, and thermal decomposition was performed in 10% hydrogen and nitrogen mixture to prepare a Ni3Ga0.8Pt0.2/CC catalyst, which showed efficient electrochemical properties under an alkaline environment.
Ni3Ga0.8Pt0.2/CC catalyst exhibits excellent electrocatalytic performance in simulated seawater, has low overpotential value, high catalytic activity, and has good stability in alkaline environments, which is better than most existing catalysts.
Smart Images

Figure CN119877007A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electrocatalysis technology and specifically relates to a Ni3Ga 0.8 Pt 0.2 / CC catalyst and its preparation method and application. Background Art
[0002] In the field of renewable energy, hydrogen energy has attracted attention due to its high efficiency and environmental protection characteristics. Hydrogen energy refers to a form of clean energy that uses hydrogen as an energy carrier. The preparation of hydrogen is closely related to the development of hydrogen energy. So far, water electrolysis is considered to be a clean and sustainable method for hydrogen production. However, the traditional water electrolysis method has the problems of low efficiency and high cost, so the development of efficient catalysts is crucial to improve the efficiency of water electrolysis hydrogen reaction.
[0003] By designing and optimizing the catalyst structure, the catalytic activity and stability can be improved, thereby reducing energy consumption and reducing costs. Platinum (Pt) is one of the most commonly used HER catalysts, with high catalytic activity and stability, but its scarcity and high cost limit its development in large-scale applications.
[0004] In recent years, as the technology of binary alloy electrocatalysts has gradually matured, existing work has shifted from the preparation of binary alloy electrocatalysts to the study of more complex ternary alloy systems. Ternary alloys show better electrocatalytic performance than binary alloys, which is attributed to the synergistic effect between all three elements, which can form more diversified active sites. These sites have stronger adsorption and activation capabilities for specific reactions, thereby improving catalytic efficiency. At the same time, ternary alloys can flexibly adjust the catalytic performance, and optimize the electronic structure of the catalyst by changing the ratio of each metal element in the alloy; the various metal elements in the ternary alloy can adjust the electron distribution on the catalyst surface, form a more favorable electronic structure, promote the transfer of electrons and the adsorption of reactants, and thus improve the selectivity and activity of the catalytic reaction. However, although the existing ternary alloy catalysts can reduce the overpotential of hydrogen evolution reaction (HER) or oxygen evolution reaction (OER), their activity is still not comparable to that of pure noble metal catalysts (such as Pt or Ir-based catalysts). At the same time, in acidic or alkaline electrolytes, non-noble metals (such as Ni, Co) in ternary alloys are easily dissolved or oxidized, resulting in the loss of catalyst activity.
[0005] Therefore, the development of efficient, low-cost and highly stable ternary alloy catalysts is crucial to improving the efficiency of water electrolysis hydrogen reaction. Summary of the invention
[0006] In order to solve the deficiencies of the prior art, the present invention aims to provide a Ni3Ga 0.8 Pt 0.2 / CC catalyst and its preparation method and application, the metal salt is loaded on the carbon cloth by wet impregnation method, and finally Ni3Ga is obtained by thermal decomposition in 10% hydrogen and nitrogen mixed gas. 0.8 Pt 0.2 / CC catalyst, which can efficiently electrolyze simulated seawater, proves that preparing multi-element alloy catalysts by doping with suitable metal elements is an effective strategy for preparing high-performance electrocatalysts.
[0007] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0008] In a first aspect, the present invention provides a Ni3Ga 0.8 Pt 0.2 / CC catalyst, including carbon cloth and Ni3Ga supported on the carbon cloth 0.8 Pt 0.2 catalyst.
[0009] In some other embodiments, the Ni3Ga 0.8 Pt 0.2 Ni3Ga / CC catalyst 0.8 Pt 0.2 The loading amount of the catalyst is 55-60wt%, wherein the loading amounts of Ni, Ga and Pt are 30-40wt%, 10-15wt% and 10-15wt% respectively;
[0010] The Ni3Ga 0.8 Pt 0.2 / The particle size of CC catalyst is 150-250nm;
[0011] Preferably, the Ni3Ga 0.8 Pt 0.2 Ni3Ga / CC catalyst 0.8 Pt 0.2 The loading amount of the catalyst is 57wt%, wherein the loading amounts of Ni, Ga and Pt are 35wt%, 12wt% and 10wt% respectively;
[0012] The Ni3Ga 0.8 Pt 0.2 The particle size of the / CC catalyst is 200 nm.
[0013] In a second aspect, the present invention provides the Ni3Ga 0.8 Pt 0.2 The preparation method of the CC catalyst comprises the following steps:
[0014] (1) mixing the carbon cloth, the nickel source, the gallium source and the platinum source and adding the mixture into water for immersion to obtain a mixture;
[0015] (2) The mixture is dried and reduced to obtain Ni3Ga 0.8 Pt 0.2 / CC catalyst.
[0016] In some other embodiments, in step (1),
[0017] The molar ratio of the nickel source, gallium source and platinum source is (2.5-3.0): (0.7-0.9): (0.1-0.3);
[0018] The impregnation is ultrasonic dispersion for 10-30 minutes and impregnation for 10-15 hours;
[0019] Preferably, the molar ratio of the nickel source, gallium source and platinum source is 3.0:0.8:0.2;
[0020] The impregnation is carried out by ultrasonic dispersion for 20 minutes and impregnation for 12 hours.
[0021] In some other embodiments, before mixing, the carbon cloth is pretreated, and the pretreatment method is to immerse the carbon cloth in a mixed solution of acetone and ethanol, vacuum dry it, then put it into a sulfuric acid solution, wash it with water until it is neutral, and finally vacuum dry it;
[0022] Preferably, the pretreatment method is: the soaking temperature is 25-30°C, the volume ratio of acetone to ethanol is 1:(1-3), the vacuum drying temperature is 55-60°C, the vacuum drying time is 10-12h, and the sulfuric acid solution is a solution of sulfuric acid and water in a volume ratio of 1:(1-2).
[0023] In some other embodiments, in step (1), the nickel source is one or more of nickel nitrate, nickel chloride and nickel sulfate;
[0024] The gallium source is one or more of gallium nitrate, gallium chloride and gallium sulfate;
[0025] The platinum source is one or more of chloroplatinic acid, lithium chloroplatinate and platinum acetylacetonate.
[0026] In some other embodiments, in step (2), the drying temperature is 80-120° C. and the drying time is 10-15 h;
[0027] The reduction temperature is 600-800°C, the time is 1-5h, and the atmosphere is a hydrogen-nitrogen mixed gas;
[0028] Preferably, the reduction temperature is 700° C., the time is 2 hours, and the hydrogen-nitrogen mixed gas is a hydrogen-nitrogen mixed gas with a volume ratio of 10%.
[0029] In a third aspect, the present invention provides the Ni3Ga 0.8Pt 0.2 / Application of CC catalyst in hydrogen production by water electrolysis.
[0030] In some other embodiments, the water is simulated seawater; preferably, the simulated seawater is water containing 1 M KOH and 0.1 M NaCl.
[0031] In a fourth aspect, the present invention provides a method for producing hydrogen by electrolyzing water, using the Ni3Ga 0.8 Pt 0.2 / CC catalyst is used as a catalyst for hydrogen production by water electrolysis in a 1M KOH environment.
[0032] The beneficial effects are as follows:
[0033] The present invention adopts the surface functionalization deposition method and hydrogen reduction method to synthesize a new alloy catalyst Ni3Ga 0.8 Pt 0.2 / CC, can efficiently electrolyze simulated seawater, has excellent electrochemical performance in alkaline environment, and the catalyst is -10mA cm -2 The LSV overpotential value under the condition is 26mV, which is better than the performance of most catalysts. Characterizations such as EXAFS and XPS show that there is electron transfer between the three metals, electron perturbation occurs between the Pt site and the carbon cloth support, and the charge redistribution directly accelerates the water adsorption behavior of the Ni site and the Pt site during the catalytic process, thereby promoting the electrochemical reaction. Through the electron transfer between Ni and Ga, more electrons are transferred to Ga, and the high-valent Ni reduces the hydrogen adsorption rate and the binding energy of the reaction intermediates, thereby accelerating the process of the electrocatalyst hydrogen evolution reaction (HER). BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The scanning electron microscope image of the catalyst prepared in Example 1, wherein (a) is a partial enlarged image of (b);
[0035] Figure 2 It is a transmission electron microscope image of the catalyst prepared in Example 1, wherein (b) is a partial enlarged image of (a);
[0036] Figure 3 XRD patterns of the catalysts prepared in Example 1 and Comparative Examples 1 and 2;
[0037] Figure 4 XPS of the catalyst prepared in Example 1, including (a) Ni 2p, (b) Ga2p and (c) Pt4f diagrams;
[0038] Figure 5 (a) EXAFS spectra and (b) Fourier transforms of the catalysts prepared in Example 1 and Comparative Examples 2, 3, and 5;
[0039] Figure 6 EXAFS wavelet transform analysis of the catalyst (a) and (b) platinum foil prepared in Example 1;
[0040] Figure 7 HER LSV curves of the catalysts prepared in Example 1 and Comparative Examples 2-5 in a 1M KOH alkaline environment;
[0041] Figure 8 HER LSV curves of the catalysts prepared in Example 1 and Comparative Example 5 in an alkaline simulated seawater environment;
[0042] Fig. 9 HER LSV curves of the catalysts prepared in Example 1 and Comparative Examples 6-7 in a 1M KOH alkaline environment;
[0043] Fig.10 HER LSV curves of the catalysts prepared in Example 1 and Comparative Examples 8-9 in a 1M KOH alkaline environment;
[0044] Fig.11 HER LSV curves of the catalysts prepared in Example 1 and Comparative Example 10 in a 1 M KOH alkaline environment. DETAILED DESCRIPTION
[0045] The overall inventive concept adopted by the present invention is: to improve the catalytic activity and stability by designing and optimizing the catalyst structure, thereby reducing energy consumption and reducing costs. Platinum (Pt) is one of the most commonly used HER catalysts at present, with high catalytic activity and stability, but due to the scarcity and high cost of platinum, its development in large-scale applications is limited. Therefore, research and development of platinum alloy catalysts, under the interaction of different metal cations in the alloy catalyst, one of the metals regulates the electron distribution of another metal ion through its electron giving ability or accepting ability, and a ligand effect occurs, thereby affecting the properties and catalytic performance of the catalytic active sites, and improving the hydrogen production efficiency. Carbon cloth (CC), as an electrocatalyst carrier, has shown many advantages in the field of electrochemistry, especially when it is used as a supporting material to carry active catalysts. Carbon cloth as a carrier has good high conductivity, high surface area, mechanical strength and stability. Therefore, in the catalyst preparation process, its high specific area and stability as a carrier enable the catalyst particles to be uniformly and stably deposited on the catalyst surface without affecting the catalytic reaction.
[0046] The present invention adopts the surface functional deposition method to prepare Ni3Ga on 1*2cm carbon cloth. 0.8 Pt 0.2 / CC catalyst, which was prepared by reduction with 10% hydrogen-nitrogen mixed gas at 700°C.0.8 Pt 0.2 The Pt content in the / CC catalyst is low, but as an electrocatalyst for HER, the ternary alloy Ni3Ga 0.8 Pt 0.2 / CC shows extremely high alkaline HER catalytic activity compared with other binary alloys. At the same time, its catalytic performance was evaluated by electrolysis of seawater to simulate hydrogen production. The results show that Ni3Ga 0.8 Pt 0.2 / CC catalysts can efficiently electrolyze simulated seawater. Preparing trimetallic nanocatalysts by doping with appropriate metal elements is an effective strategy for preparing high-performance electrocatalysts.
[0047] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.
[0048] The pretreatment method of the carbon cloth is as follows: to reduce the glue and oil attached to the surface of the carbon cloth, first, soak it in a mixed solution of acetone and ethanol (volume ratio of 1:1) at a temperature of 30 degrees for fifteen minutes, and then dry it in a vacuum drying oven at 60 degrees for one night to remove the residual ethanol and acetone. Next, immerse the dried carbon cloth in a sulfuric acid solution (H2SO4:H2O, volume ratio of 1:1) for one hour, and then wash the carbon cloth with deionized water until it is neutral. Finally, the pretreated carbon cloth is vacuum dried overnight at 60 degrees.
[0049] 1. Preparation of Catalyst
[0050] Example 1
[0051] Ni3Ga 0.8 Pt 0.2 The steps for preparing the / CC catalyst by wet impregnation method are as follows:
[0052] The pretreated carbon cloth was mixed with 0.3771g nickel nitrate, 0.0664g gallium nitrate and 0.0240g chloroplatinic acid and placed in a beaker (100mL), wherein the molar ratio of Ni / Ga / Pt was 3 / 0.8 / 0.2, and the total metal ion ratio was 1.6mmol. Distilled water was used to cover the metal salt and carbon cloth, ultrasonicated for 20 minutes, and immersed for 12 hours. After immersion for 12 hours, the solution was placed in an oven and dried at 100°C for 12 hours until the water was completely discharged. Afterwards, it was reduced in a tubular furnace at 700°C for 2 hours in a 10% hydrogen and nitrogen mixed atmosphere.
[0053] Comparative Example 1
[0054] The difference from Example 1 is that no chloroplatinic acid is added to prepare Ni3Ga 0.8 / CC catalyst, the specific preparation steps are as follows:
[0055] The pretreated carbon cloth was mixed with 0.3771g nickel nitrate and 0.0664g gallium nitrate in a beaker (100mL), wherein the molar ratio of Ni / Ga was 3 / 0.8, and the total metal ion ratio was 1.55mmol. Distilled water was used to cover the metal salt and carbon cloth, ultrasonicated for 20 minutes, and immersed for 12 hours. After immersion for 12 hours, the solution was placed in an oven and dried at 100°C for 12 hours until the water was completely discharged. Afterwards, it was reduced in a tubular furnace at 700°C for 2 hours in a 10% hydrogen and nitrogen mixed atmosphere.
[0056] Comparative Example 2
[0057] The difference from Example 1 is that no gallium nitrate is added to prepare Ni3Pt 0.2 / CC catalyst, the specific preparation steps are as follows:
[0058] The pretreated carbon cloth was mixed with 0.3771g nickel nitrate and 0.0240g chloroplatinic acid and placed in a beaker (100mL), wherein the molar ratio of Ni / Pt was 3 / 0.2, and the total metal ion ratio was 1.35mmol. Distilled water was used to cover the metal salt and carbon cloth, ultrasonicated for 20 minutes, and immersed for 12 hours. After immersion for 12 hours, the solution was placed in an oven and dried at 100°C for 12 hours until the water was completely discharged. Afterwards, it was reduced in a tubular furnace at 700°C for 2 hours in a 10% hydrogen and nitrogen mixed atmosphere.
[0059] Comparative Example 3
[0060] The difference from Example 1 is that no nickel nitrate is added to prepare Ga 0.8 Pt 0.2 / CC catalyst, the specific preparation steps are as follows:
[0061] The pretreated carbon cloth was mixed with 0.0664g of gallium nitrate and 0.0240g of chloroplatinic acid and placed in a beaker (100mL), wherein the molar ratio of Ga / Pt was 0.8 / 0.2, and the total metal ion ratio was 0.3mmol. Distilled water was used to cover the metal salt and carbon cloth, ultrasonicated for 20 minutes, and immersed for 12 hours. After immersion for 12 hours, the solution was placed in an oven and dried at 100°C for 12 hours until the water was completely discharged. Afterwards, it was reduced in a tubular furnace at 700°C for 2 hours in a 10% hydrogen and nitrogen mixed atmosphere.
[0062] Comparative Example 4
[0063] The difference from Example 1 is that nickel nitrate and gallium nitrate are not added to prepare Pt 0.2 / CC catalyst, the specific preparation steps are as follows:
[0064] The pretreated carbon cloth was mixed with 0.0240 g of chloroplatinic acid and placed in a beaker (100 mL). Distilled water was used to cover the metal salt and carbon cloth, and ultrasonic treatment was performed for 20 minutes and then impregnated for 12 hours. After 12 hours of impregnation, the solution was placed in an oven and dried at 100°C for 12 hours until the water was completely discharged. Afterwards, the solution was reduced in a tubular furnace at 700°C for 2 hours in a 10% hydrogen and nitrogen mixed atmosphere.
[0065] Comparative Example 5
[0066] The preparation steps of commercial Pt / C catalyst are as follows:
[0067] 480 μL of anhydrous ethanol solution, 20 μL of nafion solution and 5 mg of Pt / C sample were mixed and put into a beaker (10 mL). After sufficient stirring, ultrasonic treatment was performed for 30 min. 100 μL of the prepared Pt / C sample was evenly coated on the carbon cloth to obtain a commercial Pt / C catalyst.
[0068] Comparative Example 6
[0069] The difference from Example 1 is that the molar ratio of gallium nitrate is increased from 0.8 to 0.9 to prepare Ni3Ga 0.9 Pt 0.2 / CC catalyst, the specific preparation steps are as follows:
[0070] The pretreated carbon cloth was mixed with 0.3493g nickel nitrate, 0.0908g gallium nitrate and 0.0201g chloroplatinic acid in a beaker (100mL), wherein the molar ratio of Ni / Ga / Pt was 3 / 0.9 / 0.1 respectively. The metal salt and carbon cloth were covered with distilled water, ultrasonicated for 20 minutes, and impregnated for 12 hours. After 12 hours of impregnation, the solution was placed in an oven and dried at 100°C for 12 hours until the water was completely discharged. Afterwards, it was reduced in a tubular furnace at 700°C for 2 hours in a 10% hydrogen and nitrogen mixed atmosphere.
[0071] Comparative Example 7
[0072] The difference from Example 1 is that the molar ratio of gallium nitrate is reduced from 0.8 to 0.7, and the molar ratio of chloroplatinic acid is increased from 0.2 to 0.3 to prepare Ni3Ga 0.7 Pt 0.3 / CC catalyst, the specific preparation steps are as follows:
[0073] The pretreated carbon cloth was mixed with 0.3329 g nickel nitrate, 0.0769 g gallium nitrate and 0.0395 g chloroplatinic acid and placed in a beaker (100 mL), wherein the molar ratio of Ni / Ga / Pt was 3 / 0.7 / 0.3 respectively. The metal salt and carbon cloth were covered with distilled water, ultrasonicated for 20 minutes, and immersed for 12 hours. After immersion for 12 hours, the solution was placed in an oven and dried at 100°C for 12 hours until the water was completely discharged. Afterwards, it was reduced in a tubular furnace at 700°C for 2 hours in a 10% hydrogen and nitrogen mixed atmosphere.
[0074] Comparative Example 8
[0075] The difference from Example 1 is that the reduction temperature is lowered from 700°C to 600°C, and the reduction time remains unchanged to prepare Ni3Ga 0.8 Pt 0.2 / CC catalyst, the specific preparation steps are as follows:
[0076] The pretreated carbon cloth was mixed with 0.3771g nickel nitrate, 0.0664g gallium nitrate and 0.0240g chloroplatinic acid and placed in a beaker (100mL), wherein the molar ratio of Ni / Ga / Pt was 3 / 0.8 / 0.2, and the total metal ion ratio was 1.6mmol. Distilled water was used to cover the metal salt and carbon cloth, ultrasonicated for 20 minutes, and immersed for 12 hours. After immersion for 12 hours, the solution was placed in an oven and dried at 100°C for 12 hours until the water was completely discharged. Afterwards, it was reduced in a tubular furnace at 600°C for 2 hours in a 10% hydrogen and nitrogen mixed atmosphere.
[0077] Comparative Example 9
[0078] The difference from Example 1 is that the reduction temperature is increased from 700°C to 800°C, and the reduction time remains unchanged to prepare Ni3Ga 0.8 Pt 0.2 / CC catalyst, the specific preparation steps are as follows:
[0079] The pretreated carbon cloth was mixed with 0.3771g nickel nitrate, 0.0664g gallium nitrate and 0.0240g chloroplatinic acid and placed in a beaker (100mL), wherein the molar ratio of Ni / Ga / Pt was 3 / 0.8 / 0.2, and the total metal ion ratio was 1.6mmol. Distilled water was used to cover the metal salt and carbon cloth, ultrasonicated for 20 minutes, and immersed for 12 hours. After immersion for 12 hours, the solution was placed in an oven and dried at 100°C for 12 hours until the water was completely discharged. Afterwards, it was reduced in a tubular furnace at 800°C for 2 hours in a 10% hydrogen and nitrogen mixed atmosphere.
[0080] Comparative Example 10
[0081] The difference from Example 1 is that pretreated nickel foam (NF) is used instead of treated carbon cloth (CC) as a carrier to prepare Ni3Ga 0.8 Pt 0.2 / NF catalyst, the specific preparation steps are as follows:
[0082] The pretreated nickel foam was mixed with 0.3771g nickel nitrate, 0.0664g gallium nitrate and 0.0240g chloroplatinic acid and placed in a beaker (100mL), wherein the molar ratio of Ni / Ga / Pt was 3 / 0.8 / 0.2, and the total metal ion ratio was 1.6mmol. The metal salt and carbon cloth were submerged with distilled water, ultrasonicated for 20 minutes, and impregnated for 12 hours. After 12 hours of impregnation, the solution was placed in an oven and dried at 100°C for 12 hours until the water was completely discharged. Afterwards, it was reduced in a tubular furnace at 700°C for 2 hours in a 10% hydrogen and nitrogen mixed atmosphere.
[0083] The pretreatment method of the nickel foam is as follows: the nickel foam is cut into the same size as the carbon cloth in Example 1, immersed in a hydrochloric acid solution (10 ml HCl + 50 mL water) and ultrasonically treated for 30 min to remove the oxide layer on the surface. The nickel foam is washed with deionized water until neutral and dried. The nickel foam is then immersed in an acetone / ethanol solution and ultrasonically treated for 10-30 min, and rinsed with deionized water.
[0084] 2. Performance Characterization
[0085] Figure 1 The SEM images of the catalyst prepared in Example 1, wherein (a) is a partial enlarged image of (b). Figure 1 It can be seen that Ni3Ga 0.8 Pt 0.2 / CC catalyst particle size is 150-200nm, Ni3Ga 0.8 Pt 0.2 / CC catalysis achieves uniform and high-density growth on the carbon cloth substrate; the high-density loading effectively increases the exposure of active sites, thereby significantly enhancing its catalytic activity in the electrolyte environment, while more effectively utilizing the high conductivity and three-dimensional porous structure advantages of the carbon cloth substrate, providing an efficient reaction interface for the electrocatalytic process.
[0086] Figure 2 Figure 1 is a transmission electron microscope image of the catalyst prepared in Example 1, wherein (b) is a partial enlarged image of (a). Figure 2 It can be seen that in Ni3Ga 0.8 Pt 0.2In the high-resolution transmission electron microscopy (HRTEM) image of the / CC composite material, two clear lattice fringes with interlayer spacing of 0.206nm and 0.272nm can be found, corresponding to the (111) crystal plane of Ni (PDF#04-001-0091) and the (110) crystal plane of Ni3Pt (PDF#01-074-6872), respectively. 0.8 Pt 0.2 The slightly increased interlayer spacing of the Ni (111) plane in / CC may be due to the interaction between Pt / Ga elements and Ni elements. The synergistic effect between different elements can significantly optimize the electronic structure, thereby significantly enhancing the Ni3Ga 0.8 Pt 0.2 / CC catalytic activity in alkaline HER.
[0087] Figure 3 The XRD patterns of the catalysts prepared in Example 1 and Comparative Examples 1 and 2 are shown in FIG. Figure 3 It can be seen that Ni3Ga 0.8 The diffraction peaks of / CC at 2θ=44.3°, 51.6°, and 75.9° correspond to the (111), (200), and (220) crystal planes, respectively, which are the same as the standard X-ray diffraction pattern of Ni face-centered cubic structure (PDF#04-001-1136). 0.8 Pt 0.2 / CC,Ni3Pt 0.2 / CC and Ni3Ga 0.8 / CC diffraction peak position, Ni3Ga 0.8 Pt 0.2 / CC and Ni3Pt 0.2 The diffraction peak position corresponding to Ni in the / CC composite material shifts to a lower 2theta value, which indicates the incorporation of Pt elements and the formation of a small amount of Ni3Pt alloy on the surface of the catalyst particles. 0.8 Pt 0.2 / CC and Ni3Pt 0.2 The X-ray diffraction pattern of / CC shows diffraction peaks at 2θ=42.2° and 49.2°, which correspond to the diffraction peaks of Ni3Pt (PDF#01-01-0091). Figure 2 The results of transmission electron microscopy images are consistent.
[0088] In order to further study the surface chemical composition, metal composition and electronic state of the catalyst, Ni3Ga 0.8 Pt 0.2 The / CC catalysts were further characterized by X-ray photoelectron spectroscopy (XPS). Figure 4 As shown, (a) Ni 2p, (b) Ga 2p and (c) Pt4f diagram. The study of catalytic systems involves complex and diverse interactions, among which the electronic interactions between the supported Ni, Ga and Pt trimetallics are crucial. Adjustment of the electronic structure of the elements can reduce the binding energy of the reaction intermediates, thereby improving the HER catalytic activity. Figure 4 The results show that the interaction of each metal during the reduction process leads to electron transfer of Pt metal nanoparticles, especially electron transfer from Pt atoms to Ni metal particles. During the reduction reaction in the preparation process, Pt combines with a part of Ni. This part of Ni shows the ability to absorb electrons from Pt. After some electrons are absorbed by Ni atoms, Pt shows a lower reduction state, which can be observed by the position of the Pt 4f peak in XPS, which is located at 71.88eV, corresponding to Ni atoms in a lower oxidation state. At the same time, during the reduction reaction, another part of Ni combines with Ga. This part of Ni shows the ability to transfer electrons from Ga. After some electrons are absorbed by Ga atoms, Ni shows a lower reduction state, which can be observed by the position of the Ga2p peak in XPS, which is located at 1118.15eV. The valence between Ni and Ga makes Ni have a relatively high valence state. The higher valence state may reduce the hydrogen adsorption rate and promote the reduction of the binding energy of the reaction intermediates, thereby accelerating the HER process. In short, electron transfer between metals plays a vital role in the electronic structure and chemical properties of the catalyst.
[0089] EXAFS was used to further verify the existence of electron transfer between metals. Figure 5 (a) EXAFS spectra and (b) Fourier transforms of the catalysts prepared in Example 1 and Comparative Examples 2, 3, and 5. Figure 5 As shown in (a), in the energy range of 11550 eV to 11600 eV, compared with the catalysts prepared in Example 1 and Comparative Examples 2, 3, and 5, the Ni3Ga 0.8 Pt 0.2 The Pt / CC catalyst exhibits a weaker absorption signal, which is due to the interaction between Pt and carbon cloth and the electron transfer with Ni. Figure 5 In (b), the horizontal axis is approximately At , both curves show different peaks, which indicates the existence of Pt-Pt bonds in this distance range. At , all four curves show different peaks, which indicates that the peaks in this range represent Pt-Pt bonds, but we can see that Ni3Ga 0.8 Pt 0.2 / CC and Ni3Pt 0.2 / CC catalysts have a shift in the Pt-Pt peak, which indicates the interaction between Ni and Pt. The peak at 0.8 Pt 0.2 There is a strong interaction between Pt and carbon cloth in / CC, which is due to the Ni3Ga 0.8 Pt 0.2 Electron transfer caused by the passage of current between Pt and carbon cloth at the interface in / CC during the hydrogen evolution reaction.
[0090] Figure 6 EXAFS wavelet transform analysis of the catalyst (a) and platinum foil (b) prepared in Example 1. Figure 6 In the EXAFS wavelet transform analysis shown in Figure 2, Pt-C bonds appear in Ni3Ga 0.8 Pt 0.2 The position of the specific abscissa of the / CC catalyst represents the interaction between Pt and C. The Ni-Pt bond can also be seen, which represents the electron transfer between Pt and Ni. The interaction between Pt and Ni can be better determined by comparing the wavelet transformed spectrum of the Pt foil.
[0091] The Ni3Ga 0.8 Pt 0.2 / CC catalysts and their electrochemical HER performance. Using mercury oxide electrode (HgO) as the reference electrode, 1 cm 2 The Pt electrode was used as the counter electrode and Ni3Ga 0.8 Pt 0.2 / CC catalyst was used as the working electrode, 1 M KOH was used as the electrolyte, and the test was carried out using Shanghai Chenhua CHI760e electrochemical workstation.
[0092] Test parameters: Linear voltammetry (LSV) test with a scan rate of 5 mV / s and a scan range of -2 to -0.6 V relative to reversible hydrogen electrode (RHE). Cyclic voltammetry test with a scan rate of 50 mV / s and a scan range of 0 to -5 V (relative to RHE).
[0093] All the obtained potentials were converted into the potential of the reversible hydrogen electrode (RHE), and the formula was: E(RHE)=E(Hg / HgO)+0.098+0.059pH.
[0094] Table 1 shows the Ni3Ga 0.8 Pt 0.2 / CC catalyst and other comparison samples' water electrolysis hydrogen production performance. Figure 7The linear voltammetry (LSV) curves of the catalysts prepared in Example 1 and Comparative Examples 2-5 are shown. Figure 7 It can be seen that Ni3Ga 0.8 Pt 0.2 The overpotential of the Ni3Pt / CC catalyst is as low as 26 mV, which is better than the 54 mV of commercial Pt / C. 0.2 The overpotential of the / CC catalyst is 51 mV, which is close to the 54 mV of commercial Pt / C. 0.8 Pt 0.2 The overpotential of the / CC catalyst is higher, which may be due to the fact that Ni as a transition metal provides more empty orbitals, generates feedback bonds, promotes electron transfer, and thus improves the electrocatalytic performance of the catalyst. 0.8 Pt 0.2 The curve of / CC is more stable, with the minimum slope of 20.78mV·dec -1 , better than the 38.35mV·dec of commercial Pt / C -1 .
[0095] Table 1 HER performance of catalysts prepared in Example 1 and Comparative Examples 2-5 in 1M KOH environment
[0096]
[0097] The corresponding overpotential is when the current density is 10 mA / cm 2 mV / dec refers to the change in potential when the current density changes by one order of magnitude, and dec is the abbreviation of decade.
[0098] Figure 8 Table 2 shows the Ni3Ga prepared in Example 1 0.8 Pt 0.2 LSV comparison of Pt / C in Pt / CC and Comparative Example 5 in alkaline simulated seawater (1M KOH+0.1M NaCl). Figure 8 It can be seen that Ni3Ga 0.8 Pt 0.2 / CC at 10mA cm -2 The overpotential at the current density is 25 mV, which is better than the 38 mV of commercial Pt / C. At the same time, according to the Tafel slope calculated in Table 2, it is found that Ni3Ga 0.8 Pt 0.2 / CC shows a lower Tafel slope than commercial Pt / C. From the above data, it can be concluded that Ni3Ga 0.8 Pt 0.2 The catalytic performance of Pt / CC electrocatalyst in electrolysis of simulated seawater is superior to that of commercial Pt / C.
[0099] Table 2 HER performance of catalysts prepared in Example 1 and Comparative Example 5 in alkaline simulated seawater environment
[0100]
[0101] a) The corresponding overpotential refers to the current density of the front column of 10mA / cm 2 mV / dec refers to the change in potential when the current density changes by one order of magnitude, and dec is the abbreviation of decade.
[0102] Fig. 9 Table 3 shows the LSV comparison of the catalysts prepared in Example 1 and Comparative Examples 6 and 7 under 1M KOH environment. 0.8 Pt 0.2 / CC at 10mAcm -2 The overpotential under current density is the smallest, far superior to Ni3Ga 0.7 Pt 0.3 / CC and Ni3Ga 0.9 Pt 0.1 / CC, from which it can be concluded that the optimal molar ratio of Ni:Ga:Pt is 3:0.8:0.2.
[0103] Table 3 HER performance of catalysts prepared in Example 1 and Comparative Examples 6 and 7 under 1M KOH environment
[0104]
[0105] a) The corresponding overpotential refers to the current density of the front column of 10mA / cm 2 The overpotential at that time.
[0106] Fig.10 Table 4 shows the LSV comparison of the catalysts prepared in Example 1 and Comparative Examples 8 and 9 in 1M KOH solution. As the calcination temperature in the tubular furnace increases, the degree of metal reduction in the hydrogen and nitrogen mixed atmosphere affects the electrochemical activity of the catalyst. 0.8 Pt 0.2 / CC has the best electrochemical activity and the lowest overpotential after calcination at 700℃. From the above data, it can be concluded that Ni3Ga 0.8 Pt 0.2 The optimal calcination temperature of the / CC electrocatalyst is 700℃.
[0107] Table 4 HER performance of catalysts prepared in Example 1 and Comparative Examples 8 and 9 in 1M KOH environment
[0108]
[0109] a) The corresponding overpotential refers to the current density of the front column of 10mA / cm 2 The overpotential at that time.
[0110] Fig.11 Table 5 shows the LSV comparison of the catalysts prepared in Example 1 and Comparative Example 10 in 1M KOH solution. 0.8 Pt 0.2 / CC at 10mAcm -2 The overpotential at the current density is 25mV, which is better than Ni3Ga 0.8 Pt 0.2 / NF 76mV. During the hydrogen evolution reaction, the current flows through Ni3Ga 0.8 Pt 0.2 The electron transfer between Pt and carbon cloth at the / CC interface leads to a strong interaction between Pt sites and carbon cloth. 0.8 Pt 0.2 The electrochemical performance of / CC electrocatalyst is better than that of Ni3Ga 0.8 Pt 0.2 / NF.
[0111] Table 5 HER performance of catalysts prepared in Example 1 and Comparative Example 10 in 1M KOH environment
[0112]
[0113] a) The corresponding overpotential refers to the current density of the front column of 10mA / cm 2 The overpotential at that time.
[0114] The above embodiments are only used to explain the technical solutions provided by the present invention and cannot limit the present invention. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention fall within the protection scope of the technical solutions of the present invention.
Claims
1. A Ni3Ga 0.8 Pt 0.2 / CC catalyst, characterized in that Including carbon cloth and Ni3Ga loaded on carbon cloth 0.8 Pt 0.2 catalyst.
2. Ni3Ga according to claim 1 0.8 Pt 0.2 / CC catalyst, characterized in that The Ni3Ga 0.8 Pt 0.2 Ni3Ga / CC catalyst 0.8 Pt 0.2 The loading amount of the catalyst is 55-60wt%, wherein the loading amounts of Ni, Ga and Pt are 30-40wt%, 10-15wt% and 10-15wt% respectively; The Ni3Ga 0.8 Pt 0.2 / The particle size of CC catalyst is 150-250nm; Preferably, the Ni3Ga 0.8 Pt 0.2 Ni3Ga / CC catalyst 0.8 Pt 0.2 The loading amount of the catalyst is 57wt%, wherein the loading amounts of Ni, Ga and Pt are 35wt%, 12wt% and 10wt% respectively; The Ni3Ga 0.8 Pt 0.2 The particle size of the / CC catalyst is 200 nm.
3. A Ni3Ga according to claim 1 or 2 0.8 Pt 0.2 / CC catalyst preparation method, characterized in that, The following steps are involved: (1) mixing the carbon cloth, the nickel source, the gallium source and the platinum source and adding the mixture into water for immersion to obtain a mixture; (2) The mixture is dried and reduced to obtain Ni3Ga 0.8 Pt 0.2 / CC catalyst.
4. Ni3Ga according to claim 3 0.8 Pt 0.2 / CC catalyst preparation method, characterized in that, In step (1), the molar ratio of the nickel source, gallium source and platinum source is (2.5-3.0): (0.7-0.9): (0.1-0.3); The impregnation is ultrasonic dispersion for 10-30 minutes and impregnation for 10-15 hours; Preferably, the molar ratio of the nickel source, gallium source and platinum source is 3.0:0.8:0.2; The impregnation is carried out by ultrasonic dispersion for 20 minutes and impregnation for 12 hours.
5. Ni3Ga according to claim 4 0.8 Pt 0.2 / CC catalyst preparation method, characterized in that, In step (1), before mixing, the carbon cloth is pretreated, and the pretreatment method is to immerse the carbon cloth in a mixed solution of acetone and ethanol, vacuum dry it, immerse it in a sulfuric acid solution, wash it with water until it is neutral, and finally vacuum dry it; Preferably, the pretreatment method is: the soaking temperature is 25-30°C, the volume ratio of acetone to ethanol is 1:(1-3), the vacuum drying temperature is 55-60°C, the vacuum drying time is 10-12h, and the sulfuric acid solution is a solution of sulfuric acid and water in a volume ratio of 1:(1-2).
6. Ni3Ga according to claim 3 0.8 Pt 0.2 / CC catalyst preparation method, characterized in that, In step (1), the nickel source is one or more of nickel nitrate, nickel chloride and nickel sulfate; The gallium source is one or more of gallium nitrate, gallium chloride and gallium sulfate; The platinum source is one or more of chloroplatinic acid, potassium chloroplatinate and platinum acetylacetonate.
7. Ni3Ga according to claim 3 0.8 Pt 0.2 / CC catalyst preparation method, characterized in that, In step (2), the drying temperature is 80-120° C. and the drying time is 10-15 h; The reduction temperature is 600-800°C, the time is 1-5h, and the atmosphere is a hydrogen-nitrogen mixed gas; Preferably, the reduction temperature is 700° C., the time is 2 hours, and the hydrogen-nitrogen mixed gas is a hydrogen-nitrogen mixed gas with a volume ratio of 10%.
8. A Ni3Ga as claimed in claim 1 or 2 0.8 Pt 0.2 / Application of CC catalyst in hydrogen production by water electrolysis.
9. The use according to claim 8, characterized in that: The water is simulated seawater; preferably, the simulated seawater is water containing 1M KOH and 0.1M NaCl.
10. A method for producing hydrogen by electrolysis of water, characterized in that: The Ni3Ga according to claim 1 or 2 0.8 Pt 0.2 / CC catalyst is used as a catalyst for hydrogen production by water electrolysis in a 1M KOH environment.
Citation Information
Patent Citations
High-loading-capacity metal monatomic catalyst and preparation method thereof
CN116607166A
Platinum-based self-supporting electro-catalytic material, preparation method and application
CN118996471A
A method of preparing a catalyst and a catalyst prepared from the method
WO2022115042A1